National Systems of Child Protection Understanding the International Variability and Context for Developing Policy and Practice - Merkel-Holguin, Lisa; Fluke, John D.; Krugman, Richard D. (Child Maltreatment, Contemporary Issues in Research and Policy, 2019)
This volume provides a wide spectrum description analysis of the contemporary and well established child protection systems in a range of countries, such as Australia, Canada, Netherlands and Spain. It presents a brief orientation about the public and private systems involved in protecting children in each country. Further the book identifies current key policy and implementation drivers that orient the systems of child protection, such as children's rights, family preservation, use of evidence and public health orientation. Finally it presents a critical analysis of the strengths and limitations of the systems, as well as, strategies for prospects for improving outcomes for children and their families. .